Cannabidiol Regulates PPARγ-Dependent Vesicle Formation as well as Cell Death in A549 Human Lung Cancer Cells - Yoon-Jong Park; Han-Heom Na; In-Seo Kwon; Yu-Na Hwang; Hye-Jin Park; Tae-Hyung Kwon; Jin-Sung Park; Keun-Cheol Kim (MDPI AG, 2022)
Extracts of phytocannabinoids from Cannabis sativa have been studied for therapeutic purposes. Although nonpsychoactive CBD has been studied as a promising anticancer drug because it induces apoptosis in many cancer cells, it is also known to induce several physiological changes. In this study, we clarify the functional role it plays in the morphological characteristics of intracellular vesicle formation as well as apoptosis in A549 human lung cancer cells. CBD treatment shows growth inhibition at concentrations above 20 μM, but FACS analysis shows low efficacy in terms of cell death. Microscopic observations suggest that multiple vesicles were detected in the cytoplasmic region of CBD-treated A549 cells. CBD treatment upregulates apoptosis-related proteins, such as p53, PARP, RIP1, RIP3, Atg12, and Beclin, indicating that CBD regulates several types of cell death. CBD treatment also induced E-cadherin, PPARγ, clathrin, β-adaptin, and Tsg101, also known to be cellular-differentiation inducers or vesicle-formation components. Treatment combining CBD with GW9662, a PPARγ inhibitor, reduced CBD-induced cytoplasmic vesicle formation. This indicates that PPARγ regulates the vesicle-formation mechanism. However, CBD-treated E-cad KO clones did not show this regulatory mechanism. These results elucidate the pharmacological and molecular networks associated with CBD in PPARγ-dependent vesicle formation and the induction of apoptosis.